Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T16:25:53+01:00
Y+2-(3-x)=0
x-2=5-(2-y)

y+2-3+x=0
x-2=5-2+y

y-1+x=0
x=y+5

y+y=-4
x=y+5

2y=-4
x=y+5

y=2
x=7

b)3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

x=3y+8
9y-15y+9y=5-24

x=3y+8
3y=19

y=19/3
x=27
  • Użytkownik Zadane
2010-02-02T16:26:44+01:00
Y+2-(3-x)=0
x-2=5-(2-y)

y-1+x=0
x-2=5-2+y

y+x=1
x-y=3+2

2x=6
x=3

y=1-x
y=-2

b)

3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8 /*-2
3x-6y=5

-14x+6y=-16
3x-6y=5

11x=-11
x=-1

-6y=5-3x
-6y=5+3
-6y=8
y=-8/6=-4/3
2010-02-02T16:29:33+01:00
A) y+2-3+x=0 b) 3x-3y+4x=8
x-2=5-2+y 3x-15y=5-9y

y+x=-1 -x-3y=8 /*3
x-y=5 3x-6y=5

2x=4 -3x+9y=24
x=2 3x-6y=5

2-y=5 3y=29
y= -3 y=9 i 1/9

x=19 i 2/5